Energy management of fuel cell electric vehicles based on working condition identification of energy storage systems, vehicle driving performance, and dynamic power factor. (October 2020) - Gharibeh, Hamed Farhadi; Yazdankhah, Ahmad Sadeghi; Azizian, Mohammad Reza
Highlights: Working condition identification of battery based on formulation of combined efficiency. Formulation of hydrogen fuel value of fuel cell by considering the efficiency of power electronic converters. Vehicle driving condition identification based on formulation of operation state vehicle function. Dynamic power factor formulation to prevent excess charge of battery. Abstract: Energy management strategy is one of the main challenges in the development of fuel cell electric vehicles equipped with various energy storage systems. The energy management strategy should be able to provide the power demand of the vehicle in different driving conditions, minimize equivalent fuel consumption of fuel cell, and improve the total efficiency of energy storage systems. This paper presents a new bi-level online energy management for a battery-based fuel cell electric vehicle based on operational mode control, state machine control, equivalent consumption minimization, and dynamic power factor strategies. The purpose of this paper is the identification of vehicle driving conditions, determination of hydrogen fuel value based on fuel cell output power, classification of battery state of charge based on battery combined efficiency, and optimal power distribution of energy storage systems. This strategy works such that the battery charging is done at the optimum point of the fuel cell in order to increase the total efficiency of energy storage systems and satisfy subsequent maximum instantaneous power in different driving conditions. The proposed bi-level energy management strategy obtains significant simulation results, including a reduction in fuel consumption, reduction in power fluctuations, and increment in the energy efficiency of energy storage systems compared to other energy management strategies. Graphical abstract: Image, graphical abstract